Hypoxic and osmotic expression of Kir2.1 potassium channels in retinal pigment epithelial cells: Contribution to vascular endothelial growth factor expression. (October 2021) - Klose, Eva; Kuhrt, Heidrun; Kohen, Leon; Wiedemann, Peter; Bringmann, Andreas; Hollborn, Margrit
Abstract: Retinal pigment epithelial (RPE) cells express different subtypes of inwardly rectifying potassium (Kir) channels. We investigated whether human and rat RPE cells express genes of strongly rectifying Kir2 channels. We also determined the hypoxic and hyperosmotic regulation of Kir2.1 gene expression in cultured human RPE cells and the effects of siRNA-mediated knockdown of Kir2.1 on VEGFA expression, VEGF secretion, proliferation, and viability of the cells. Extracellular hyperosmolarity was induced by addition of NaCl or sucrose. Hypoxia and chemical hypoxia were produced by cell culture in 0.25% O2 and addition of CoCl2, respectively. Gene expression levels were evaluated by real-time RT-PCR. Rat RPE cells contained Kir2.1, Kir2.2, Kir2.3, and Kir2.4 gene transcripts while human RPE cells contained Kir2.1, Kir2.2, and Kir2.4 transcripts. Immunocytochemical data may suggest that Kir2.1 protein in cultured human cells is expressed in both perinuclear and plasma membranes. Kir2.1 gene expression and Kir2.1 protein level in human cells increased under hypoxic and hyperosmotic conditions. The expression of the Kir2.1 gene was mediated in part by diverse intracellular signal transduction pathways and transcription factor activities under both conditions; the hyperosmotic, but not the CoCl2 -induced Kir2.1 gene expression was dependent on intracellular calcium signaling. Autocrine/paracrine activation of purinergic receptors contributed to Kir2.1 gene expression under hyperosmotic (P2Y1, P2Y2, P2X7 ) and CoCl2 -induced conditions (P2Y2, P2X7 ). Exogenous VEGF, TGF-β1, and blood serum decreased Kir2.1 gene expression. Inhibition of VEGF receptor-2 increased the Kir2.1 gene expression under control conditions and in CoCl2 -simulated hypoxia, and decreased it under high NaCl conditions. Knockdown of Kir2.1 by siRNA inhibited the CoCl2 -induced and hyperosmotic transcription of the VEGFA gene and caused a delayed decrease of the constitutive VEGFA gene expression while VEGF protein secretion was not altered. Kir2.1 knockdown stimulated RPE cell proliferation under control and hyperosmotic conditions without affecting cell viability. The data indicate that Kir2.1 channel activity is required for the expression of the VEGFA gene and inhibits the proliferation of RPE cells. Under control and hypoxic conditions, the extracellular VEGF level may regulate the production of VEGF via its inhibitory effect on the Kir2.1 gene transcription; this feedback loop may prevent overproduction of VEGF. Highlights: RPE cells express genes of the Kir2 potassium channel family. Kir2.1 gene is activated by hypoxia and hyperosmolarity. Kir2.1 channel activity is required for VEGF gene expression. VEGF inhibits Kir2.1 gene expression. Kir2.1 channel activity inhibits proliferation of RPE cells.